IDENTIFIKASI PEWARNA SINTETIK AURAMIN DAN KUNING METANIL PADA PERMEN MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI - Tyasna Salsabila, Aninda; Iskandar, Damayanti; Herfiani, Dita (DE FACTO : Journal Of International Multidisciplinary Science, 2025)
Food is food or drink that must be guaranteed food safety for human consumption. One aspect of food safety that needs to be considered is the use of Food Additives (FA). Food additives are materials added to food to influence the nature or shape of the food, an example is dye. Some enterpreneurs use dyes to give food colors that are more striking, such as using dyes in candy. However, the dyes used by entrepreneurs are synthetic dyes not for food, such as auramine and methanyl yellow. The use of auramine and methanyl yellow dyes in candy can be identified using High Performance Liquid Chromatography (HPLC) through chromatogram results. The research results obtained were that x candy did not contain auramine and methanyl yellow dyes. In the results of the chromatogram research, the 1st repeat and 2nd repeat candy samples did not have an area at the retention time of the auramine and methanyl yellow standard solution.